Strategi Pemasaran Dalam Mempertahankan Eksistensi Industri Pengerajin Tas di Tanggulangin (studi kasus CV. Parikesit) - muhammad nuzulaturrayhan; Lilik Indayani; Rizky Eka Febriansah (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2025)
CV. Parikesit is one of the leather bag artisan industries located in the INTAKO Tanggulangin area. The purpose of this study was to determine the Marketing Strategy in Maintaining the Existence of the Bag Craftsman Industry in Tanggulanin (Case Study of CV. Parikesit). Approach this research method uses descriptive qualitative methods so that data collection techniques are carried out by means of observation, interviews, and documentation. The data analysis technique used in this study uses 3 stages, namely data reduction, data presentation, and conclusion drawing. The results showed that the marketing strategy in maintaining the existence of CV. Parikesit uses 3 ways, namely product marketing strategies, strategies in processing raw materials, and labor management. In marketing its products CV. Parikesit does 2 ways of selling, namely through offline and online. In managing raw materials CV. Parikesit uses 2 leather materials, namely genuine leather derived from cowhide and synthetic leather derived from the remaining raw materials for shoes, by using 2 different skins it can produce products with different selling values. In the labor management of CV employees. Parikesit, like what the owner of CV. Parikesit by organizing 2 classes of employees in his business, namely daily workers and piecework. Daily workers who work 6 days a week who will work on all orders according to the target and the specified deadline, while for piecework workers who work on products only on demand